Occult cystobiliary communication presenting as postoperative biliary leakage after hydatid liver surgery: Are there significant preoperative clinical predictors? - Demircan, Orhan (Canadian Medical Association, 2006)
BACKGROUND: Occult cystobiliary communication (CBC) presents with biliary leakage, if the cystobiliary opening cannot be detected and repaired at operation. We investigated the clinical signs associated with the risk of occult CBC in the preoperative period by studying patients who developed biliary leakage after hydatid liver surgery. METHODS: We analyzed the records of 191 patients treated for hydatid liver cyst. Postoperative biliary leakage developed in 41 patients (21.5%). Independent predictive factors were established by logistic regression analysis using clinical parameters, whose cutoff values were determined by receiver operating characteristic (ROC) curves. RESULTS: Postoperative biliary leakage presented as external biliary fistula in 31 (75.6%) of 41 patients, as biliary peritonitis in 6 (14.6%) and as cyst cavity biliary abscess in 4 (9.8%). Independent clinical predictors of occult CBC, represented by biliary leakage, were alkaline phosphatase > 250 U/L, total bilirubin > 17.1 μmol/L, direct bilirubin > 6.8 μmol/L, γ-glutamyl transferase > 34.5 U/L, eosinophils > 0.09 and cyst diameter > 8.5 cm. Multilocular or degenerate cysts increased the risk of biliary leakage (p = 0.012). Postoperative complication rates were 53.7% in the patients with biliary leakage, and 10.0% (p < 0.001) in those without. The mean postoperative hospital stay was longer in patients with biliary leakage (14.3 [and standard deviation SD 1.9] d) than in those without (7.3 [SD 2.3] d) (p < 0.001). Nineteen (61.3%) of 31 biliary fistulae closed spontaneously within 10 days. The remaining 12 (38.7%) fistulae closed within 7 days after endoscopic sphincterotomy. CONCLUSION: Factors that predict occult CBC due to hydatid liver cyst were identified. These factors should allow the likelihood of CBC to be determined and, thus, indicate the need for additional procedures during operation to prevent the complications of biliary leakage.